Object-oriented programming with Smalltalk - Wertz, H. (Harald), 1947- (London : ISTE Press, 2015)
Filling the gap for an in-depth self-study reference, and permitting readers to master all aspects of object-oriented programming through a large set of exercises with highly detailed resources, this book uses a pedagogical approach to cover all aspects of object-oriented programming. --
Online resource; title from PDF title page (EBSCO, viewed December 9, 2015).
Includes bibliographical references and index.
Keywords: Object-oriented programming (Computer science); Smalltalk (Computer program language); COMPUTERS -- Programming -- Object Oriented; COMPUTERS -- Programming Languages -- General; Object-oriented programming (Computer science); Smalltalk (Computer program language); Electronic books